Are totally recycled hot mix asphalts a sustainable alternative for road paving? - Silva, Hugo Manuel Ribeiro Dias da (2012)
The recycling of reclaimed asphalt pavement (RAP) helps road authorities to achieve their goal of a sustainable road transport system by reducing waste production and resources consumption. The environmental and economic benefits of using RAP in hot mix asphalt (HMA) applications could be pushed up to the limit, by producing totally recycled HMAs (100% RAP), but the performance of this alternative must be satisfactory. In fact, these mixtures could possibly present problems of workability and durability, higher binder aging and low fatigue cracking resistance. Thus, the objective of this study is to determine if totally recycled HMA mixtures could be a good solution for road paving, by evaluating the merit of some rejuvenator agents (commercial product; used engine oil) in improving the aged binders’ properties and the recycled mixture performance. Several binder samples were prepared with the mentioned rejuvenators and characterized (Pen, R&B and dynamic viscosity), in order to select the best rejuvenator contents. The production temperatures of the corresponding recycled mixtures were evaluated based on their workability. Totally recycled HMAs were produced with the best previously observed combinations, and their performance (water sensitivity, rutting resistance, stiffness, fatigue resistance, binder aging) was assessed. The main conclusion of this study is that totally recycled HMAs can be a good alternative for road paving, especially if rejuvenator agents are used to reduce their production temperature and to improve their performance.